CREATIVE CITIES AND THE TOURIST EXPERIENCE: AN ANALYSIS OF THE KNOWLEDGE PRODUCED AND A LISTENING ON CREATIVE RECIFE - Paes-Cesário, Marília (Brazilian Creative Industries Journal, 2022)
The creative cities have presented themselves as a new and distinct way of offering attractions to tourists, and these new possibilities have resulted in differentiated and unique experiences for those who not only enjoy but also frequently participate in the creative processes. As a result of this knowledge gap, this article has the following objectives: to relate what has recently been published in one of the main databases in the literature on creative cities and the tourist experience; to detect the objectives and contexts of research on creative cities and the tourist experience; and to identify what has been done in Recife - PE/Brazil - which is one of UNESCO’s creative cities - to encourage, enhance, and disseminate the creative potential of this city. As a methodology for selecting what has been published, criteria for article selection were established using keywords such as creative cities, tourism, and tourist experience. Furthermore, a synthesis of knowledge on this topic was possible, allowing perception of what is already known about the topic and what still needs to be researched, as well as pointing out directions for future investigations and some limitations of studies in this area. Because some study gaps were identified, it is possible to conclude that the themes of creative cities related to the tourist experience have the potential to be much more researched. The main limitation of this study is the fact that it is a systematic review of the literature, through only one database, and therefore, it is suggested as relevant for future research an updated systematic review, since many other works arise daily.